Perioperative cancer cell dissemination detected with a real-time RT-PCR assay for EpCAM is not associated with worse prognosis in pancreatic ductal adenocarcinoma - Sergeant, Gregory; Roskams, Tania; van Pelt, Jos; Houtmeyers, François; Aerts, Raymond; Topal, Baki (BMC cancer, 2011)
Background Epithelial cell adhesion molecule (EpCAM) has been used as surrogate marker for the quantification of circulating tumour cells (CTC). Our aim was to prospectively study the value of a real-time RT-PCR assay for EpCAM detection in the peripheral blood and peritoneal cavity of patients undergoing pancreatectomy for pancreatic ductal adenocarcinoma (PDAC). Methods From 48 patients with PDAC (40 resectable, 8 unresectable) and 10 patients with chronic pancreatitis undergoing pancreatectomy 10 ml of venous blood was drawn preoperatively (PB) and postoperatively (POB, day 1 (D1B), day 7 (D7B) and after 6 weeks (6WB). Of all patients undergoing pancreatectomy, 40 ml peritoneal lavage fluid was taken preoperatively and postoperatively. A real-time RT-PCR assay (TaqMan, ABI Prism 7700) was developed for the detection of EpCAM mRNA. To discriminate between EpCAM-positive and negative samples a cut-off was applied. Median postoperative follow-up was 24.0 months (range: 0.7 - 41.3). Results PB was EpCAM-positive (+) in 25% of patients versus 65% of patients in POB (p < 0.0001). EpCAM(+) was noted at D1B, D7B and 6WB was found in 28.6%, 23.1% and 23.5% of patients respectively. Preoperative peritoneal lavage fluid was EpCAM(+) in 10.3% versus 53.8% of patients postoperatively (p < 0.0001). At none of the time-points, an association was found between EpCAM positivity in blood and/or peritoneal cavity and cancer-specific or disease-free survival. Also, no significant associations were found between clinicopathological variables and perioperative EpCAM positivity. Conclusions Despite a significant increase in EpCAM counts in postoperative blood and peritoneal lavage fluid this was not associated with worse prognosis after pancreatectomy for PDAC. Trial registration Clinicaltrials.gov NCT00495924